Pendampingan Desain dan Renovasi Toilet Inklusif bagi Penyandang Disabilitas - Parmonangan Manurung; Stefani Natalia Sabatini (Jurnal Atma Inovasia, 2026)
Accessible and usable toilets are essential components of an inclusive built environment for persons with disabilities, particularly in community-based health facilities. This article presents a community service program that assisted the design and renovation of toilets at Rumah Kebugaran Difabel (RKD) in Sedayu, Bantul, within the Keluarga Difabel Pinilih ecosystem. RKD provides affordable, accessible, community-based health services for persons with disabilities, but its facility—a former auxiliary public health center—contained three underutilized toilets that no longer met accessibility requirements. The program adopted a participatory assistance approach informed by participatory action research, inclusive design, and user-centered design. Activities included needs identification, existing-condition audits, user-needs mapping, design development, user testing, and refinement of renovation recommendations. The resulting design addressed the needs of wheelchair users, crutch users, persons with visual, hearing, and physical impairments by integrating accessibility and usability principles. Two toilets were designated for general users, while one was redesigned as an accessible toilet, accompanied by a more user-friendly ablution facility. Direct involvement of persons with disabilities in the audit and testing stages improved design accuracy and strengthened the potential to create safe, dignified, and independent sanitation facilities. The program demonstrates that successful toilet renovation in existing buildings requires collaboration among architectural standards, structural constraints, and users’ lived experiences.